EVALUATION OF ANTICANCER ACTIVITY OF FLAVONOID ISOLATED FROM THE ACETONE EXTRACT OF THE AERIAL PARTS OF PHYLLANTHUS NIRURI AGAINST HUMAN LUNG CANCER CELL LINE (A549) - N. PADMAPRIYA,; T.V. POONGUZHALI, (International Journal of Pharma and Bio Sciences, 2015)
Phyllanthus niruri L. (Euphorbiaceae), known as “quebra-pedra” (Portuguese for “stonebreaker”), is an herb used for kidney disorders.Whole plants have been used in traditional medicine for treatment of jaundice, asthma, hepatitis and malaria. The present study was designed to determine the anticancer activity of flavonoid isolated from the acetone extract of the aerial part of P. niruri against human lung cancer cell line (A549).MTT assay based cytotoxic activity study against human lung cancer cell line (A549) was conducted to evaluate the potent activity of flavonoid isolated from P. niruri.TLC and GC- MS analysis were recorded to confirmthe presence of flavonoids in acetone extracts.Flavonoids isolated from the acetone extract of the aerial part of P.niruri showed cytotoxic activity against the human lung cancer cell line (A549) and the inhibitory concentration at 50% growth (IC50) was found to contain IC50 = 30.70±0.81µg/mL respectively. The results indicated that the flavonoids isolated from the P.niruri showed cytotoxic activity which can be effectively employed in anticancer treatment. Cytotoxic study suggested that flavonoid from the acetone extract of the aerial part of P. niruri was found to contain maximum inhibition of 66.6% at 7.8µg/mL concentration.